2018
DOI: 10.1177/1940082918809617
|View full text |Cite
|
Sign up to set email alerts
|

Status of Large Terrestrial Vertebrates in the Monteverde-Arenal Bioregion, Northwestern Costa Rica

Abstract: Protected areas have been important in reducing tropical forest biodiversity loss. Costa Rica has been a model country in protecting forests and promoting conservation. However, many Costa Rican protected areas are surrounded by highly modified habitat and may be losing species, either because they are too small to support viable populations or are too isolated to allow for population connectivity. We used camera traps to study terrestrial mammal and terrestrial bird populations in the Monteverde-Arenal Bioreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 40 publications
0
6
0
2
Order By: Relevance
“…In fact, viable jaguar populations may only occur in only two of the areas of this study: the reserves of the Guanacaste Conservation Area and the Central Volcanic Mountain Range (Sanderson et al 2002, SINAC 2018b, although our analysis indicates these are also too small to survive in the long-term (Thomas 1990). A recent camera study of the MAB found that jaguars were very rare (and probably non-viable) in that isolated (although relatively large, about 50,000 ha) conservation area (Zamzow et al 2018). However, if the sub-corridors proposed here were established and protected, they would increase connectivity, presumably increasing the combined population size in all protected areas from the Guanacaste region to the Central Volcanic Mountain Range (jaguar conservation unit 154 in Sanderson et al 2002).…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…In fact, viable jaguar populations may only occur in only two of the areas of this study: the reserves of the Guanacaste Conservation Area and the Central Volcanic Mountain Range (Sanderson et al 2002, SINAC 2018b, although our analysis indicates these are also too small to survive in the long-term (Thomas 1990). A recent camera study of the MAB found that jaguars were very rare (and probably non-viable) in that isolated (although relatively large, about 50,000 ha) conservation area (Zamzow et al 2018). However, if the sub-corridors proposed here were established and protected, they would increase connectivity, presumably increasing the combined population size in all protected areas from the Guanacaste region to the Central Volcanic Mountain Range (jaguar conservation unit 154 in Sanderson et al 2002).…”
Section: Discussionmentioning
confidence: 57%
“…Guanacaste and Santa Rosa NPs, SINAC 2018b) but is very rare or absent in other protected areas (e.g. MAB, Zamzow et al 2018). Therefore, if sub-corridor protection were to be initiated, this species could also be monitored in areas where it is currently absent or rare as a measure of whether our proposal was having some conservation success.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rarity of observations of melanistic oncillas in this region may, however, indicate that this is a random mutation rather than an adaptive advantage. While non-melanistic oncillas have been observed in recent mammal studies in the Monteverde Region (Zamzow et al 2018), observations are notably rare and much less frequently recorded than its more common Leopardus relatives and puma (Personal communication; JE Rogan unpublished data) and it is possible it was misidentified due to its strong resemblance to margay (Zamzow et al 2018). Further research efforts to gauge the frequency of melanistic oncillas in the area will be key to better understanding this incredible phenomenon in this elusive species.…”
mentioning
confidence: 99%